Did COVID-19 pandemic have any impact on suicide trends in India? Insights from the National Crime Records Bureau data - Pooja Singh; Niraj Pandit; Rucha Dave; Maharshi Patel (Archives of Mental Health)
Introduction: This study reviewed the impact of the COVID-19 pandemic on suicide trends and sociodemographic profiles in India using data from the National Crime Records Bureau (NCRB). Methods: The study collected data on suicide-related information from the official publications of the NCRB for the years 2017–2022. Suicide data from January 2017 to December 2022 were analyzed. Results: The suicide rate per 100,000 population increased from 9.9 in 2017 to 12.4 in 2022, indicating a rising trend. Males consistently had higher suicide numbers, increasing from 89,019 in 2017 to 122,724 in 2022, a 37.9% rise. Female suicides increased from 40,852 in 2017 to 48,172 in 2022, a 17.9% rise. The trend line indicates a constant increase in the suicide rate, with an R2 = 0.96. It is consistent in pre- and post-COVID-19 era. Conclusion: The study revealed that there was a steady increase in suicide from 2017 to 2022. There is no any serious rise of the suicide rate during or post-COVID-19 pandemic, and the increase was constant. Looking to this, there is an urgent need to take action to prevent suicides in India.